RNA–Protein Interactions That Regulate Pre-mRNA Splicing - Singh, Ravinder (Gene Expr, 2018)
Splicing of nuclear precursor messenger RNAs is an important and ubiquitous type of gene regulation in metazoans. Splicing joins the coding sequences called exons by removing the intervening noncoding sequences, introns, from primary transcripts. Alternative splicing generates an enormous repertoire of functional diversity by producing multiple RNAs and proteins from a single gene. In fact, recent genome sequences from several organisms suggest that splicing regulation is likely to provide an important source of functional diversity in more complex organisms. Because splice sites are short sequences at the ends of introns, the functional splice sites have to be distinguished from an excessively large number of sequences in the primary transcripts that resemble a splice site. Furthermore, alternative splice sites have to be correctly chosen at appropriate times. Thus, selection of proper splice sites remains a daunting biological problem. This review focuses on a few examples in which the molecular and biochemical basis for splice site selection is better understood.